ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF SILVER NANOPARTICLES AGAINST NEISSERIA GONORRHOEAE AND CANDIDA ALBICANS - Tantyani, Tasha Anandya; Taufikurohmah, Titik (International Journal of Research -GRANTHAALAYAH, 2020)
This Research on the antibacterial and antifungal activity of nanosilver against Neisseria gonorrhoeae and Candida albincas fungi has been carried out. The purpose of this study was to determine antibacterial activity of nanosilver against Neisseria gonorrhoeae and antifungal activity against Candida albincas. Synthesis Nanosilver uses bottom up method and characterized using UV-Vis Spectrophotometer. Nanosliver concentrations used were 30, 40, 50, and 60 ppm. Antibacterial and antifungal activity tests using disk diffusion method. Observations obtained in form of the presence or absence of clear zones formed around paper discs indicate the inhibition of nanosilver on microbial growth. The results of testing the antifungal activity of Candida albicans on nanosilver with concentrations of 30, 40, 50 and 60 ppm resulted in clear zones of 9.73 nm, 11.46 nm, 11.93 nm, and 13 nm with fungal inhibition response categories is medium and strong. The results antibacterial activity test of Neisseria gonorrhoeae on nanosilver with concentrations of 30, 40, 50 and 60 ppm did not show any clear zone around the disc, it showed that nanosilver in this study did not have antibacterial activity against Neisseria gonorrhoeae.